2005
DOI: 10.1007/s11095-005-8176-x
|View full text |Cite
|
Sign up to set email alerts
|

Cubosome Dispersions as Delivery Systems for Percutaneous Administration of Indomethacin

Abstract: MO dispersions can be proposed as nanoparticulate systems able to control the percutaneous absorption of indomethacin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
81
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(81 citation statements)
references
References 35 publications
0
81
0
Order By: Relevance
“…In this context, Table 2 displays representative examples from literature on studies conducted on the possibility of utilizing cubosomes and hexosomes as drug nanocarriers [52,53,[108][109][110]. These nanostructured fluids show potential as drug nanocarriers since they are composed of naturally occurring biodegradable lipids and tailored for solubilizing higher amounts of amphiphilic, hydrophobic, and hydrophilic drugs in their highly ordered self-assembled interiors as opposed to liposomes.…”
Section: Cubosomes and Hexosomes As Drug Nanocarriersmentioning
confidence: 99%
“…In this context, Table 2 displays representative examples from literature on studies conducted on the possibility of utilizing cubosomes and hexosomes as drug nanocarriers [52,53,[108][109][110]. These nanostructured fluids show potential as drug nanocarriers since they are composed of naturally occurring biodegradable lipids and tailored for solubilizing higher amounts of amphiphilic, hydrophobic, and hydrophilic drugs in their highly ordered self-assembled interiors as opposed to liposomes.…”
Section: Cubosomes and Hexosomes As Drug Nanocarriersmentioning
confidence: 99%
“…The feasibility of cubosomes as carriers for parenteral, topical, and buccal delivery of drugs has been reported in the literature (14)(15)(16)(17)(18)(19). Formulations based on this technology have been reported to have improved tolerance and drug bioavailability (20).…”
Section: Introductionmentioning
confidence: 99%
“…In cubosome system, it was speculated that cubic structure with similar nano-structure as the skin, increase the interaction between skin and formulation and enhances the skin permeation. 5,20) Lopes et al reported that hexagonal phase may facilitate the fusion of the LCNs with stratum corneum and deeper skin layers and thereby may improve drug delivery to the skin. 14) Moreover, they speculated that the larger surface area of the hexosome system might have resulted in enhanced contact with the porcine ear skin that improved vitamin K permeation.…”
Section: F-nmr (Right Side) Spectra Of Glyceryl Monooleyl Ether (Gme)mentioning
confidence: 99%
“…4) Among these LLC systems, some of liquid crystal structures form a liquid crystalline nanoparticles (LCNs) by dispersing in an aqueous environment and the LCNs of reverse hexagonal phase and bicontinuous cubic phase are called "hexosomes (H II )" and "cubosomes," respectively. 3,5) Glycerol monoolate (GMO) has been widely studied as an additive to form LLCs and their LCNs.6,7) Effect of the additives such as block copolymer formation and electrostatic interaction were also investigated.8-11) Cohen-Avrahami et al reported transdermal delivery of sodium diclofenac with hexosomes of GMO in combination with cell-penetrating peptides. 3,12) Lopes et al showed improved skin permeation for vitamin K and cyclosporine A with hexosomes of GMO.…”
mentioning
confidence: 99%
See 1 more Smart Citation